A Study On Glass Ceiling Effect In Banking: Perceptions Of Women Employees Across Job Levels In Hyderabad - Gopisetti, Mr. Uma Srikanth; G.Jothi, Dr. (Metallurgical and Materials Engineering, 2025)
Despite the implementation of gender equity policies in the banking sector, a persistent glass ceiling continues to affect women bank employees. This study investigates the attitudes of women working in public and private banks in Hyderabad District toward the glass ceiling and explores how these attitudes impact their career development. A structured questionnaire using a 5-point Likert scale was distributed among 120 women bank employees. The study employed quantitative analysis, including descriptive statistics and chi-square tests, to understand the relationship between job level and the perception of the glass ceiling. Results indicated significant associations between job level and the perceived existence of the glass ceiling. The findings highlight the importance of addressing systemic barriers to foster a more equitable workplace environment for women in banking.